2016
DOI: 10.1002/app.44373
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity andEMIshielding effectiveness of polyurethane foam–conductive filler composites

Abstract: The morphological, electrical, and thermal properties of polyurethane foam (PUF)/single conductive filler composites and PUF/hybrid conductive filler composites were investigated. For the PUF/single conductive filler composites, the PUF/nickel‐coated carbon fiber (NCCF) composite showed higher electrical conductivity and electromagnetic interference shielding effectiveness (EMI SE) than did the PUF/multiwall carbon nanotube (MWCNT) and PUF/graphite composites; therefore, NCCF is the most effective filler among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Different types of fillers and nanofillers, such as cellulose and lignocellulosic fibers [ 138 , 139 ], glass wool, glass microspheres or glass fibers [ 180 , 181 , 182 ], egg shell wastes [ 140 ], date palm particles [ 141 ], walnut and hazelnut shells [ 142 ], and esparto wool [ 143 ], just to mention a few, can be used to improve the structural and mechanical properties of PUFs. Despite having a significant effect on the thermal and electrical properties, materials such as carbon nanotubes (CNTs) [ 183 , 184 , 185 , 186 ], graphene [ 187 , 188 , 189 , 190 ], EG [ 35 ], carbon nanofibers (CNFs) [ 191 ], or inorganic fillers, such as Fe 3 O 4 [ 192 ], TiO 2 [ 193 ], and iron oxide [ 194 ] are also commonly used to improve the structural and mechanical properties of the foams.…”
Section: Polyurethane Foams Applications and Enhancement Of Propermentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of fillers and nanofillers, such as cellulose and lignocellulosic fibers [ 138 , 139 ], glass wool, glass microspheres or glass fibers [ 180 , 181 , 182 ], egg shell wastes [ 140 ], date palm particles [ 141 ], walnut and hazelnut shells [ 142 ], and esparto wool [ 143 ], just to mention a few, can be used to improve the structural and mechanical properties of PUFs. Despite having a significant effect on the thermal and electrical properties, materials such as carbon nanotubes (CNTs) [ 183 , 184 , 185 , 186 ], graphene [ 187 , 188 , 189 , 190 ], EG [ 35 ], carbon nanofibers (CNFs) [ 191 ], or inorganic fillers, such as Fe 3 O 4 [ 192 ], TiO 2 [ 193 ], and iron oxide [ 194 ] are also commonly used to improve the structural and mechanical properties of the foams.…”
Section: Polyurethane Foams Applications and Enhancement Of Propermentioning
confidence: 99%
“…In that sense, carbon-based nanoparticles such as EG, CNTs, graphene, and carbon black have attracted increasing interest due to their inherently high mechanical and physical properties [ 179 ]. The incorporation of these particles in PUFs has been known to enhance their mechanical performance [ 35 , 127 , 187 , 202 ]. Nowadays, due to their lower price, CNTs or graphene have been used in many applications.…”
Section: Polyurethane Foams Applications and Enhancement Of Propermentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of liquid‐type additives such as PFA, HMDS, or MWCNT/PFA hybrid additives for the improvement of the sound absorption properties of flexible PUF have not yet been reported. Recent studies of PUF with MWCNT composites suggested that a small amount of MWCNTs in the polyurethane matrix may yield copious bubble nucleation by reducing the critical activation energy for nucleation. As a result, the MWCNT particles effectively reduced the cell size of the PUF, decreasing the thermal conductivity of the PUF.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, conductive polyurethane composite foams have attracted more and more interest due to their low density and thermal insulation properties. Moreover, these materials are particularly interesting for their effectiveness in shielding electromagnetic interference, which allows their use in electronic devices where electromagnetic emissions can interfere with the operation of neighboring electronic equipment …”
Section: Introductionmentioning
confidence: 99%